Analyzing the Students’ Ability in Writing Opinion Essay using Flash Fiction - Lestari Setyowati (Journal of English Language Teaching and Linguistics, 2016)
The use of literature in language classroom has attracted language teachers to utilize it in the FL classroom. This paper is intended to decribe the students’ ability to write opinion essay by using flash fiction, Frank Stocton’s The Lady or the Tiger. The design used in the study was content analysis design in which the researcher collected the students’ composition after they were assigned to write opinion essay by using flash fiction. The subject of the study was 2013A batch of STKIP PGRI Pasuruan. The data were colected in 30 June 2015 and 7 July 2015. The result shows that students were able to make thesis statement that showed their opinion, but unable to develop the essay well, and state conclusion that reflect the essay. Moreover, two thirds of the students were not able to produce the essay in at least 250 words. The problems of the flash fiction used in the classroom and its limitation are discussed in the paper along with the suggestion for those who are interested to use literary work in FL classroom. Key words: literary works, flash fiction, opinion essay.